A Study of Thrombocytopenia in Chronic Liver Disease and Its Correlation with Development of Esophageal Varices - Jahan, Nusrat; Islam, Quazi Tarikul; Rahman Siddiqui, Md Mahmudur; Hossain, Ahmed; Hossain, S Fahmida (Bangladesh Journal of Medicine, 2022)
Background: The aim and objective of this study was to evaluate relationship of platelet count and esophageal varices in chronic liver disease (CLD) admitted in the medicine unit and gastroenterology department of Dhaka Medical College Hospital. Methods: In this cross-sectional study, a total number of 100 randomly selected, clinically diagnosed patients of chronic liver disease were studied from June 2010 to November 2010 (6 months). All patients were assessed as per Child-Pugh class and had full blood count, HBsAg, Anti-HCV antibodies by ELISA, abdominal ultrasound and Endoscopy of upper gastrointestinal tract. Patients were divided into Group A (Platelet count <1,50,000) and Group B (platelet count>1,50,000). Result: 73 male (73%) and 27 female patients (27%) with age range of 16 to 75 years were evaluated. 24% patient were in between 45-55 years age group. 63% patient fall in child Pugh class A group, 32% fall in child Pugh class B &5% fall in child Pugh class C. Esophageal varices were present in 32 patients (32%) and absent in 68 patients (68%). Group A had 31 patients (31% of the total) with 26 patients (83.87%) having esophageal varices. Group B had 69 patients (69% of the total) with 6 patients (8.70%) having esophageal varices. Sensitivity of thrombocytopenia as a marker of esophageal varices was 81.25% and specificity 92.64%, positive predictive value 83.87% and negative predictive value 91.3% and Odds ratio was 54.6. P value is <0.001. Conclusion: In this study, It was attempted to find out the relationship between thrombocytopenia and esophageal varices in CLD. In Group A that is platelet count <1,50,000, the incidence of EV was more than Group B (platelet count >1,50,000). Hence, thrombocytopenia is a good surrogate marker for the presence of esophageal varices in CLD. Bangladesh J Medicine 2022; 33: 247-251